2017
DOI: 10.1016/j.tjog.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dyslipidemia during pregnancy may increase the risk of preterm birth: A meta-analysis

Abstract: Epidemiological studies have reported an inconsistent relationship between maternal lipid levels and preterm birth (PTB). We performed this meta-analysis to evaluate the association between maternal dyslipidemia and PTB. Overall, three nested case-control studies and eight cohort studies were eligible. Effect estimates [odds ratio(OR)/relative risk] were pooled using a fixed-effects or a random-effects model. Subgroup and metaregression analyses were conducted to evaluate the sources of heterogeneity. Eleven s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 42 publications
3
51
0
3
Order By: Relevance
“…LGA [20][21][22]. Furthermore, most results with regard to a decreased risk for preterm birth was found for high HDL levels [7,[23][24][25], and the present study con rmed this association. But no relationship between HDL and preterm birth was found in a cohort study conducted in China [12].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…LGA [20][21][22]. Furthermore, most results with regard to a decreased risk for preterm birth was found for high HDL levels [7,[23][24][25], and the present study con rmed this association. But no relationship between HDL and preterm birth was found in a cohort study conducted in China [12].…”
Section: Discussionsupporting
confidence: 80%
“…Participants were healthier in their study as women with chronic conditions excluded from their analysis, which may explain the heterogeneity of the results. Similar positive association was also reported by a meta-analysis [7], but it only included studies with blood samples taken in the rst two trimesters and the de nition of preterm birth varied among studies.…”
Section: Discussionsupporting
confidence: 80%
“…However, the directions of these associations between the lipid GRS and risk for PTB are inconsistent with the hypothesized directions of effect. In particular, a higher HDL‐C GRS would be expected to confer a protective effect and higher TAG and TC GRS would be expected to confer increased risk for PTB based on previous findings in the literature (Jiang et al, ). Nevertheless, these associations were significant and remained so after adjusting for known confounders including race and ethnicity, BMI and maternal age.…”
Section: Discussionmentioning
confidence: 89%
“…Studies of maternal lipid profiles in late‐first to early‐second trimester found that low HDL‐C (Jelliffe‐Pawlowski et al, ; Kramer et al, ; Lei et al, ), high TAG (Jelliffe‐Pawlowski et al, ; Lei et al, ; Mudd et al, ; Niromanesh et al, ), low TC (Edison et al, ; Oluwole et al, ) or high TC (Maymunah et al, ; Mudd et al, ), and high LDL‐C:HDL‐C (Chatzi et al, ) were associated with increased risk for PTB. A recent meta‐analysis of these studies found that elevated TC, elevated TAG, and low HDL‐C were significantly associated with increased risk for PTB, with significant odds ratios ranging from 1.33 to 1.71 (Jiang et al, ). Elevated LDL‐C was not significantly associated with risk for PTB (Jiang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation